STATE POLICY FOR THE DEVELOPMENT OF THE CIVIL AVIATION OF THE XXI CENTURY: ECONOMIC AND STRATEGIC OPPORTUNITIES OF UKRAINE - Задорожня, Г. В.; Соколова, Є. П. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
Civil aviation using complex linkages with other sectors contributes to the economic development of nations and enjoys the fruits of such development. As the level of income and production expanding demand for aviation services rendered; at the same time, contributing to the development of tourism, trade and employment, aviation is an important tool for economic development.